Simple Underlay Myringoplasty: A Prospective Study - Budhathoki, B; Mishra, SC; Sharma, A (Journal of Nepalgunj Medical College, 2015)
Background: Chronic otitis media (COM) is highly prevalent disease encountered by an otologist world wide and also in Nepal. Myringoplasty is the treatment of choice in many cases. There are various techniques of performing myringoplasty with various types of grafts. We propose Simple Underlay Myringoplasty (SUM) using fat graft. Objective: The objective of this study was to evaluate the role of fat graft in closure of small dry central perforations by simple underlay myringoplasty (SUM) with aim to introduce SUM technique in this part of Nepal (Mid Western and Far Western Region). Methods: Young patients above 15 years of age with diagnosis of chronic otitis media, mucosal type with perforations smaller than 50% of tympanic membrane were included for fat graft myringoplasty. There were total 25 cases included for the study. All the cases were done under local anesthesia. A large single piece of fat, approximately double the size of perforation was harvested from the posterior side of ear lobule. The margin of perforation was freshened. The fat was placed like a dumbbell, equal portion lies medial and lateral to the perforation. Graft uptake results were evaluated after 4 weeks. Results: Graft uptake was successful in 23 patients (92%). Conclusion: The technique avoids extensive middle ear manipulation and it is safe, simpler procedure for the closure of a dry small central perforation. Its success rate is as good as myringoplasty using temporalis fascia in small central perforations. Journal of Nepalgunj Medical College Vol.12(1) 2014: 19-21